2019
DOI: 10.3168/jds.2019-16853
|View full text |Cite
|
Sign up to set email alerts
|

Efficient use of genomic information for sustainable genetic improvement in small cattle populations

Abstract: In this study, we compared genetic gain, genetic variation, and the efficiency of converting variation into gain under different genomic selection scenarios with truncation or optimum contribution selection in a small dairy population by simulation. Breeding programs have to maximize genetic gain but also ensure sustainability by maintaining genetic variation. Numerous studies have shown that genomic selection increases genetic gain. Although genomic selection is a well-established method, small populations st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…Populations can also alleviate the loss of genetic variability and increase sustainability by implementing optimum contribution selection. In our previous study we tested the effect of varying the use of sires in a population equal to the one simulated here (Obšteter et al, 2019). We showed that small populations can increase the genetic gain of genomic selection by 25% by rapidly turning over elite sires.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Populations can also alleviate the loss of genetic variability and increase sustainability by implementing optimum contribution selection. In our previous study we tested the effect of varying the use of sires in a population equal to the one simulated here (Obšteter et al, 2019). We showed that small populations can increase the genetic gain of genomic selection by 25% by rapidly turning over elite sires.…”
Section: Discussionmentioning
confidence: 94%
“…We simulated two populations with overlapping generations that mimicked a domestic and a foreign breeding program and differed in selection intensity and accuracy. The simulation included genomes, genetic values, and phenotypes for a polygenic trait with heritability 0.25, and a whole cattle breeding program as described previously (Obšteter et al, 2019). In short, both breeding programs started from the same base population.…”
Section: Simulation Of the Base Population And Historical Breedingmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, 1,000 QTL per chromosome was considered to be the causal loci of a polygenetic trait influenced by many genes, each of them with minor effects. The chosen number of QTL per chromosome is consistent with many published studies (e.g, Obšteter et al, 2019Obšteter et al, , 2021Selle et al, 2020). The simulated haplotypes were used to establish the founder population of 5,000 animals with 1:1 sex ratio.…”
Section: Burn-in Phasementioning
confidence: 99%
“…This, however, depends on the genetic correlation between the environments and on the initial reliability of breeding values, that is the current size of the reference population. If the size of the reference population is already large, adding more genomic information does not increase accuracies of GEBVs to a great extent (Cao et al, 2020;Obšteter et al, 2019).…”
Section: Collaboration Across Linesmentioning
confidence: 99%